Methylation of oxytocin related genes and early life trauma together shape the N170 response to human faces - Parianen, Franca; Spencer, Hannah; Montoya, Estrella R.; Kraaijenvanger, Eline J.; He, Yujie; Branje, Susan; Boks, Marco P.; Bos, Peter A. (European neuropsychopharmacology, 2020)
Childhood trauma fundamentally shapes social cognition and basic processing of social cues, which frequently cascade into adverse behavioral outcomes. Recent studies indicate that epigenetic changes in oxytocin functioning might contribute to these long-term effects, although a deeper understanding of the underlying mechanisms is still lacking. The electroencephalographic N170 response to faces might capture a neural response at the core of these interactive effects of oxytocin gene methylation and childhood adversity, given that this response is considered to reflect fundamental face processing, to be susceptible to oxytocin administration and also to be a biomarker of various psychiatric disorders. We assessed the N170 response to neutral faces in relation to participant's (81, women) recalled childhood trauma, methylation of their oxytocin structural (OXTg) and oxytocin receptor (OXTRg) genes, and endogenous levels of cortisol and testosterone. Additionally, we investigated the interactive effect of OXTg methylation and CTQ across three face sets of varying maturity. Methylation of OXTg relates to a weakened N170 response towards adults, children and infants. Moreover, methylation of both OXTRg and OXTg shaped the directionality of adversity effects, predicting a weakened N170 response in those with high methylation and hyper-vigilance with participants with low methylation. Our results are the first to relate OXT(R)g methylation to the N170 response. They shed light on biological processes linking childhood adversity and epigenetic marks to altered behavior and potentially psychopathologies.
Gesehen am 04.08.2025